2002
DOI: 10.1177/0192513x02023003004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Increasing Marital Stability in the United States

Abstract: Results from the 1995 National Survey of Family Growth indicate that marriages contracted after 1980 are becoming more stable. This article examines several individual characteristics in search of an explanation for increasing stability. A person-year file is created and logistic regression is used to determine which covariates account for the negative effect of year in a model predicting the likelihood of marital dissolution. Increasing experience of premarital sex, premarital birth, cohabitation, and racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(192 citation statements)
references
References 36 publications
(48 reference statements)
3
184
2
3
Order By: Relevance
“…Schwertfeger did not find clear patterns in divorce rates for mixed ethnic couples apart from a high level of stability for Chinese co-ethnic unions. On the other hand, Heaton's (2002) US study of mixed marriages between Blacks and Whites reported that marital dissolution was more likely for mixed ethnic couples. Kalmijn et al (2005), using linked marriage and divorce registration data from 1974 to1994 in the Netherlands, found a high risk of dissolution for couples including a Dutch person and someone from another nationality.…”
Section: Empirical Studiesmentioning
confidence: 98%
“…Schwertfeger did not find clear patterns in divorce rates for mixed ethnic couples apart from a high level of stability for Chinese co-ethnic unions. On the other hand, Heaton's (2002) US study of mixed marriages between Blacks and Whites reported that marital dissolution was more likely for mixed ethnic couples. Kalmijn et al (2005), using linked marriage and divorce registration data from 1974 to1994 in the Netherlands, found a high risk of dissolution for couples including a Dutch person and someone from another nationality.…”
Section: Empirical Studiesmentioning
confidence: 98%
“…The rate dropped after the early 1980s to 3.5 in 2008 -a one third decline (United States Census Bureau, 2012). The rise in age at first marriage since the 1980s appears to be an important factor in accounting for this decline (Heaton, 2002), because people who marry at older ages have a lower risk of divorce. In addition, delaying marriage decreases the percentage of married couples in the population, thus lowering the number of individuals at risk of divorce.…”
Section: Trends In the Divorce Ratementioning
confidence: 99%
“…One of these is later age at marriage, which is a powerful predictor of low marital dissolution rates (Booth and Edwards 1985;Moore and Waite 1981) and has been cited as a primary reason for the overall decline in marital dissolution rates since 1980 (Heaton 2002). If highly educated women are delaying marriage more than other women, this trend might explain why highly educated women's marital dissolution rates are declining while rates for less-educated women are not.…”
Section: Objective Two: Distinguish Trends By Education From Other Dementioning
confidence: 99%